Biopolymers Online 2002
DOI: 10.1002/3527600035.bpol5018
|View full text |Cite
|
Sign up to set email alerts
|

Teichoic and Teichuronic Acids from Gram‐Positive Bacteria

Abstract: Introduction Historical Outline Chemical Structures Cell Wall Teichoic Acid Teichuronic Acids Biosynthesis and Genetics of Poly(GroP) Polymerizing Enzyme System for Poly(Glycerol Phosphate) Teichoic Acid The Genetic Basis of the Biosynthesis of the Soluble Precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 141 publications
0
15
0
Order By: Relevance
“…In addition, no significant differences in expression or localization of LytF were observed in the tagE null mutant strain (Fig. 1b, 3f-g), which has a defect in glycosylation of the major WTA (Allison et al, 2011;Lazarevic et al, 2002). A previous report has demonstrated that TagE is only able to use a poly(GroP) polymer as a substrate (Allison et al, 2011).…”
Section: Expression and Localization Of Lytf In Mutants Of The Lta Symentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, no significant differences in expression or localization of LytF were observed in the tagE null mutant strain (Fig. 1b, 3f-g), which has a defect in glycosylation of the major WTA (Allison et al, 2011;Lazarevic et al, 2002). A previous report has demonstrated that TagE is only able to use a poly(GroP) polymer as a substrate (Allison et al, 2011).…”
Section: Expression and Localization Of Lytf In Mutants Of The Lta Symentioning
confidence: 95%
“…Teichoic acids are either covalently attached to PGs (wall teichoic acid, WTA) or anchored to membrane lipids (lipoteichoic acid, LTA) (Foster & Popham, 2001;Neuhaus & Baddiley, 2003). Bacillus subtilis 168 mainly produces major and minor WTAs, as well as LTA during vegetative growth (Foster & Popham, 2001;Lazarevic et al, 2002). In this organism, major WTA and LTA polymers consist of a similar main chain structure, comprising poly glycerolphosphate (GroP) repeating units (Foster & Popham, 2001;Neuhaus & Baddiley, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…subtilis 168 is the gram-positive model organism and its genome databases are quite substantial. In addition, the biosynthetic pathways of both wall-and lipo-teichoic acids are well understood (Lazarevic et al 2002;Schirner et al 2009;Wörmann et al 2011;Reichmann et al 2011). Gene inactivation procedure is fully established in this organism.…”
Section: Discussionmentioning
confidence: 99%
“…Anionic polymers are either covalently attached to the PG (wall teichoic acid [WTA]) or anchored to the membrane lipids (lipoteichoic acid [LTA]) (1,2). In Bacillus subtilis 168, the WTAs are composed of major and minor forms, and both are tethered to peptidoglycan via a linkage unit (3). The main chains of the major and minor WTAs consist of glycerol phosphate (GroP) and glucosyl-N-acetylgalactosamine 1-phosphate (GlcGalNAcP) repeats, respectively.…”
mentioning
confidence: 99%